2000
DOI: 10.1242/dev.127.23.5093
|View full text |Cite
|
Sign up to set email alerts
|

Loss- and gain-of-function mutations show a Polycomb group function for Ring1A in mice

Abstract: The products of the Polycomb group (PcG) of genes act as transcriptional repressors involved in the maintenance of homeotic gene expression patterns throughout development, from flies to mice. Biochemical and molecular evidence suggests that the mouse Ring1A gene is a member of the PcG of genes. However, genetic evidence is needed to establish PcG function for Ring1A, since contrary to all other murine PcG genes, there is no known Drosophila PcG gene encoding a homolog of the Ring1A protein. To study Ring1A fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…1a), raising the possibility that PRC1 functions in POT. To determine the function of PRC1 in POT, PRC1 function was eliminated after embryonic day 15 (E15) using Ddx4-Cre 32 to mutate the E3 ubiquitin ligase RNF2 on a background lacking its partially redundant paralog RING1 (RING1A) to create PRC1 conditional knockout (PRC1cKO) mice 12,[33][34][35] (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a), raising the possibility that PRC1 functions in POT. To determine the function of PRC1 in POT, PRC1 function was eliminated after embryonic day 15 (E15) using Ddx4-Cre 32 to mutate the E3 ubiquitin ligase RNF2 on a background lacking its partially redundant paralog RING1 (RING1A) to create PRC1 conditional knockout (PRC1cKO) mice 12,[33][34][35] (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Mice were maintained on a mixed genetic background of FVB and C57BL/6 J. Generation of mutant Ring1 ( Ring1 −/− ) and Rnf2 floxed alleles ( Ring1 F/F ) were reported previously 34 , 71 . Ring1 −/− and Ring1 F/F mice were obtained from Dr. Haruhiko Koseki.…”
Section: Methodsmentioning
confidence: 99%
“…Eed flox/flox mice were kindly provided by Dr. Weipeng Mu and Dr. Terry Magnuson (Mu et al 2014). Ring1a −/− and Ring1b flox/flox mice were previously described (del Mar Lorente et al 2000), and were kindly provided by Dr. Miguel Vidal. Both male and female mice were used in this study.…”
Section: Micementioning
confidence: 99%
“…Recent studies identified an important role for PRC2 in restricting trophoblast induction in human naïve pluripotent stem cells in vitro [ 57 , 58 ], suggesting a role in the earliest mammalian lineage decision after fertilization. In PRC1, the loss of RING1B protein results in developmental arrest at E6.5, during gastrulation, but RING1A mutants were able to survive and reach birth, although displaying defects in transformation of the axial skeleton and altered levels of Hox gene expression [ 59 , 60 ].…”
Section: Roles Of Polycomb Group Proteins In Pluripotency and Early D...mentioning
confidence: 99%